Impact of a clinical pharmacist–managed clinic in primary care mental health integration at a Veterans Affairs health system - Herbert, Christina (Ment Health Clin, 2018)
INTRODUCTION: The demand for mental health (MH) services has increased as more veterans seek MH care. At the South Texas Veterans Health Care System, Primary Care Mental Health Integration (PCMHI) was developed to manage patients with uncomplicated MH conditions, including depression, anxiety, or posttraumatic stress disorder (PTSD), within an interdisciplinary primary care (PC) team that includes clinical pharmacy specialists (CPSs). Pharmacists have improved outcomes and access to care for many chronic medical conditions, but limited data demonstrate the impact of MH pharmacists within PC. METHODS: This project evaluated the impact of a PCMHI CPS clinic on managing patients with recent antidepressant initiation and CPS clinic intake from September 2015 through December 2016, including follow-up through January 2017. Markers used to evaluate effectiveness of the service included the Patient Health Questionnaire-9 scores, antidepressant medication possession ratio, number of emergency department visits for MH-related concerns, patient engagement in concurrent psychotherapy, and referrals to specialty MH providers. RESULTS: A total of 196 unique patients had intake with the PCMHI CPS in the time specified; 172 of these patients were included in analyses. There were 155 patients maintained in PC. Average Patient Health Questionnaire-9 scores decreased from 14.5 to 8.5, with 63 patients (46%) achieving response and 42 patients (31%) achieving remission. The average antidepressant medication possession ratio was 0.93 for all included patients. DISCUSSION: A PCMHI CPS successfully manages and maintains patients with uncomplicated MH conditions in PC through evidence-based pharmacotherapy, as evidenced by symptom improvement, medication adherence, and low rate of specialty MH referrals.